Peran Grup Afiliasi dalam Memoderasi Pengaruh Hutang terhadap Nilai Perusahaan pada Perusahaan Property & Real Estate yang terdaftar di Bursa Efek Indonesia - Maulidyani, Fina; Asmapane, Set; Setiawati, Ledy (Faculty of Economics and Business Mulawarman University, 2017)
The objective of this research is to examine empirically the effect of Debt on Firms Value and the ability of Group Affiliation to moderate the effect of Debt toward Firms Value by using an approach simple linear regression and Moderated Regression Analysis (MRA). This research uses time series data in 2011 2015 for company's finance data that got from Indonesia Stock Exchange. Election Procedure sample uses purposive sampling and the result are existed 35 companies that fulfill criterion. The results show that Debt has positive effect on Firms Value, while Group Affiliation act as a moderating variable can reduce the effect of Debt toward Firms Value. The higher capability of group affiliation to take control of a company, the lower debt financing that company has.Keywords: Debt Financing, Firms Value, Group Affiliation